2014
DOI: 10.1186/s12883-014-0201-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms, predictors and clinical impact of early neurological deterioration: the protocol of the Trondheim early neurological deterioration study

Abstract: Background10-40% of patients with acute ischemic stroke (AIS) suffer an early neurological deterioration (END), which may influence their long term prognosis. Multiple definitions of END exist, even in recently published papers. In the search for causes, various biochemical, clinical, and imaging markers have been found to be associated to END after AIS in some but not in other studies.The primary aim of this study is to assess the contribution of END to functional level at 3 months post stroke measured by mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
0
14
2
Order By: Relevance
“…In spite of this, we found strong associations between neurological deterioration and prognosis. Further, patients eligible for fibrinolysis were more prone to inclusion [16]. However, adjustments for fibrinolysis did not weaken our findings.…”
Section: Strengths and Limitationscontrasting
confidence: 41%
See 2 more Smart Citations
“…In spite of this, we found strong associations between neurological deterioration and prognosis. Further, patients eligible for fibrinolysis were more prone to inclusion [16]. However, adjustments for fibrinolysis did not weaken our findings.…”
Section: Strengths and Limitationscontrasting
confidence: 41%
“…Stringent inclusion criteria applied to 46 patients [16]. During the main study, approximately 1,150 patients were discharged from the SU with AIS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most ischemic stroke patients tend to improve over the subsequent few days after symptoms onset, a sizeable fraction does not substantially recover but even deteriorates, which has been identified as early neurological deterioration (END) (Seners, Turc, Oppenheim, & Baron, ). Previous studies reported that END after acute ischemic stroke is observed in 5%–40% patients and often leads to an increasing risk of functional disability and mortality (Helleberg, Ellekjær, Rohweder, & Indredavik, ; Kwon, Lee, Bae, & Kang, ; Seners et al., ; Sun et al., ; Zhang et al., ). Accordingly, more precise understanding of the potential mechanisms involved in END could provide valuable insights for improving stroke outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical trials have suggested that albuminuria should not only be considered as a risk assessment marker but a treatment target [2,4]. END in acute ischaemic stroke is a commonly occurring event and has poor long and short term outcomes [11,12]. The predictors of END (Clinical or Radiological), in acute stroke has been repeatedly studied.…”
Section: Introductionmentioning
confidence: 99%